MODEL PEMBELAJARAN "RESOURCE -BASED LEARNING" SEBAGAI SALAH SATU MODELBELAJAR BAGI ANAK KORBAN GEMPA BUMI DIDAERAH KALIPUCANG, KASIHAN, BANTUL - Ita Maesaroh, Tuti Hayati, Ani Habibah, Novi N., dan Siti Rodiah (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
This research aims to know the influence of Resource-Based Learning as one of thelearning models for the students as the victims of the earthquake in Kalipucang, Kasihan,Bantul.This research is classified as an action research. It is a fact-finding and problemsolvingmethod in social situation to improve the action quality, involving the researcher,practitioner, and laymen. The research subject was the students as the victims ofearthquake in Kalipucang, Kasihan, Bantul. The techniques of collecting the data wereobservation, interview, questionnaire, and documentation. The data analysis employedin this research was descriptive-qualitative analysis.The result of this research reveals that Resource-Based Learning can be usedas one of the learning models for the students as the victims of earthquake in Kalipucang,Kasihan, Bantul. This can be seen from the achievement of Resource-Based Learning.The characteristics of Resource-Based Learning are 1) using any kinds of informationresource as learning resource, 2) explaining the students on the width of informationresource, 3) urging to change the passivity of the students in traditional learning withactive learning motivated by interest and self-involvement in education, 4) increasingthe learning motivation by providing any possibilities of learning materials, learningmethod, and communication media which are different from the conventional class, 5)giving a chance to the students to work or learn in accordance with their own capacity,6) being more flexible in using time and learning class and 7) developing self-confidencein learning which enables them to learn as long as their life.Key words: Learning model, Resource-Based Learning